Inside a Shari'ah Court - Films Media Group (2007)
Some democratic governments have considered allowing Muslim communities to conduct their own courts of law, or Shari'ah courts. Westerners who oppose such measures cite reports of amputation and stoning wherever Shari'ah has taken hold. This program travels to Nigeria, where Shari'ah law functions alongside the secular court system. Spotlighting an outspoken judge determined to convey the benefits of Islamic law, the film presents cases, verdicts, and sentences that clearly illustrate ways in which Shari'ah is implemented. Although the attitudes of local women toward the court may surprise some viewers, the film pulls no punches in its examination of the precarious rights of women under Shari'ah. Portions are in other languages with English subtitles. A BBC Production. (52 minutes).
fma39650
Mode of access: World Wide Web.
System requirements: Windows Media, etc.